Moderating role of place identity in parental support of children’s folk games in Chinese neighbourhoods - Zhao, Xin; Hussain, Norhuzailin; Abdul Shukor, Shureen Faris (Cogent OA, 2025)
Children’s physical and mental health are currently facing serious challenges due to decreasing outdoor activity time and an increasingly homogeneous selection of accessible games. Children’s social skills and physical development are improved by folk games, which also encourage them to interact more with the natural world. This study uses linear regression and moderating effect analyses based on a five-point Likert-scale questionnaire survey of 434 parents from four urban residential neighbourhoods in Taiyuan, China. The results show that parental support considerably impacts children’s engagement in folk games. This effect becomes even stronger when parents demonstrate moderate or higher degrees of place identity to their neighbourhood’s environment. These findings highlight the significance of promoting children’s active participation in folk games to enhance social connection and nature exploration. Additionally, parents’ emotional connections to their neighbourhoods, which are based on a sense of belonging and shared experiences, influence the requirements for play spaces. This provides valuable insights for parents, educators, urban planners and policymakers to develop or implement supportive measures that promote holistic child development and preserve cultural heritage.